The Implementation of Contextual Learning and Teaching Method in Improving Students Learning Achievement - Merlyn Rutumalessy; I Nyoman Sudyana; Achmad Abdul Azis; Suharyatun Suharyatun; Amat Suroso (Journal on Education, 2023)
High learning achievement is necessary to achieve a better life. This study aims to determine the implementation of contextual teaching and learning approach in improving students' learning achievement in fiqh subjects. This research uses a qualitative approach and observation and interview data collection techniques. The results revealed that the application of learning with the Contextual Teaching and Learning (CTL) approach, it can make it easier for students to understand and apply in the daily lives of educated participants. Educators strive for students to be actively involved in the application process so that students can easily apply discover knowledge from their new learning experiences. The application of the contextual approach has been well implemented but not yet maximized.